Cancer Detection Rates of Systematic and Targeted Prostate Biopsies after Biparametric MRI - Maudy C. W. Gayet; Anouk A. M. A. van der Aa; Harrie P. Beerlage; Bart Ph Schrier; Maaike Gielens; Roel Heesakkers; Gerrit J. Jager; Peter F. A. Mulders; Hessel Wijkstra (Prostate Cancer)
Objective. To compare prostate cancer detection rates (CDRs) and pathology results with targeted prostate biopsy (TB) and systematic prostate biopsy (SB) in biopsy-naive men. Methods. An in-patient control study of 82 men undergoing SB and subsequent TB in case of positive prostate MRI between 2015 and 2017 in the Jeroen Bosch Hospital, the Netherlands. Results. Prostate cancer (PCa) was detected in 54.9% with 70.7% agreement between TB and SB. Significant PCa (Gleason score ≥7) was detected in 24.4%. The CDR with TB and SB was 35.4% and 48.8%, respectively (p=0.052). The CDR of significant prostate cancer with TB and SB was both 20.7%. Clinically significant pathology upgrading occurred in 7.3% by adding TB to SB and 22.0% by adding SB to TB. Conclusions. There is no statistically significant difference between CDRs of SB and TB. Both SB and TB miss significant PCas. Moreover, pathology upgrading occurred more often by adding SB to TB than vice versa. This indicates that the omission of SB in this study population might not be justified.